New records of dasiops spp (diptera: lonchaeidae) associated with pasiflora grown in colombia / nuevos registros de dasiops spp (diptera: lonchaeidae) asociados a pasifloras cultivadas en colombia (2012)
Four new records for Dasiops were registered for Colombia: Dasiops brevicornis (Williston, 1896), D. rugifrons Henning 1948, D. plaumanni McAlpine 1964 y D. chotanus Korytkowski 1971. All samples were collected in McPhail traps located in passiflora crops. Aspect related with their taxonomy, biology and geographical distribution are presented. / Se registran cuatro especies del género Dasiops para Colombia: Dasiops brevicornis (Williston, 1896), D. rugifrons Henning, 1948, D. plaumanni McAlpine 1964 y D. chotanus Korytkowski 1971. Todas fueron capturadas en trampas McPhail en cultivos de pasifloras. Se presentan aspectos relacionados con su taxonomía, biología y distribución geográfica